Desenvolvimento motor de criança com paralisia cerebral: Avaliação e intervenção - Rosa, Greisy Kelli Broio; Marques, Inara; Medina-Papst, Josiane; Gobbi, Lilian Teresa Bucken [UNESP] (FapUNIFESP (SciELO), 2008)
The objective of this study was to analyze the motor development of a ten year old child with ataxic cerebral palsy and the effects of a motor activities program in the swimming pool. Motor development was measured according to the motor assessment and the intervention program of motor activities in the swimming pool conducted at Sesi/Londrina, twice a week, during 45 minute sessions over a 2 month period, with an attendance rate of 87%. Data was analyzed descriptively comparing the results with before and after tests. Generally, the motor quotient regarding all items was classified as very low, characterizing motor deficit, with exception of temporal organization, presented as normal low. After intervention, the only area that showed positive change was balance; this result showed that the child gained 12 months in motor age, without corresponding alterations in the other areas.
Motor development of children with cerebral palsy: Assessment and intervention
Keywords: Cerebral palsy; Intervention; Motor assessment; Motor development; Special education